Value for Open Space: Protection and Access Level. (4th February 2016) - Metz, Neil
Abstract: This paper analyzes the value for the fundamental properties of open space: protection and access, using home sales from Colorado. Several measures are used: adjacency, distance to the nearest tract of open space, and percentage of open space area. Results indicate protected land with access (e.g., public park) has the greatest value, followed closely by protected land without access (e.g., conservation land), while unprotected land (e.g., agricultural land) has little to no value. Nearest neighbor matching is used as an improved control for unobservable neighborhood effects, and results indicate previous studies may overestimate the small‐scale value of open space.